Genetically encoded optical sensors for monitoring of intracellular chloride and chloride-selective channel activity - Bregestovski, Piotr; Waseem, Tatyana; Mukhtarov, Marat (Frontiers in Molecular Neuroscience, 2009)
This review briefly discusses the main approaches for monitoring chloride (Cl−), the most abundant physiological anion. Noninvasive monitoring of intracellular Cl− ([Cl−]i) is a challenging task owing to two main difficulties: (i) the low transmembrane ratio for Cl−, approximately 10:1; and (ii) the small driving force for Cl−, as the Cl− reversal potential (ECl) is usually close to the resting potential of the cells. Thus, for reliable monitoring of intracellular Cl−, one has to use highly sensitive probes. From several methods for intracellular Cl− analysis, genetically encoded chloride indicators represent the most promising tools. Recent achievements in the development of genetically encoded chloride probes are based on the fact that yellow fluorescent protein (YFP) exhibits Cl−-sensitivity. YFP-based probes have been successfully used for quantitative analysis of Cl− transport in different cells and for high-throughput screening of modulators of Cl−-selective channels. Development of a ratiometric genetically encoded probe, Clomeleon, has provided a tool for noninvasive estimation of intracellular Cl− concentrations. While the sensitivity of this protein to Cl− is low (EC50 about 160 mM), it has been successfully used for monitoring intracellular Cl− in different cell types. Recently a CFP–YFP-based probe with a relatively high sensitivity to Cl− (EC50 about 30 mM) has been developed. This construct, termed Cl-Sensor, allows ratiometric monitoring using the fluorescence excitation ratio. Of particular interest are genetically encoded probes for monitoring of ion channel distribution and activity. A new molecular probe has been constructed by introducing into the cytoplasmic domain of the Cl−-selective glycine receptor (GlyR) channel the CFP–YFP-based Cl-Sensor. This construct, termed BioSensor-GlyR, has been successfully expressed in cell lines. The new genetically encoded chloride probes offer means of screening pharmacological agents, analysis of Cl− homeo